Achieving sustainable peace in post conflict societies : an evaluation of South Africa's Truth and Reconciliation Commission - Rage, Anne-Britt (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.